Assessment of In-Depth Degradation of Artificially Aged Triterpenoid Paint Varnishes Using Nonlinear Microscopy Techniques. (18th November 2014) - Filippidis, George; Mari, Meropi; Kelegkouri, Lambrini; Philippidis, Aggelos; Selimis, Aleksandros; Melessanaki, Kristallia; Sygletou, Maria; Fotakis, Costas
Abstract: The present work investigates the applicability of nonlinear imaging microscopy for the precise assessment of degradation of the outer protective layers of painted artworks as a function of depth due to aging. Two fresh and artificially aged triterpenoid varnishes, dammar and mastic, were tested. Nonlinear imaging techniques have been employed as a new diagnostic tool for determination of the exact thickness of the affected region due to artificial aging of the natural varnishes. The measured thicknesses differ from the calculated mean penetration depths of the samples. These nondestructive, high resolution modalities are valuable analytical tools for aging studies and they have the potential to provide unique in-depth information. Single photon laser induced fluorescence measurements and Raman spectroscopy were used for the integrated investigation and analysis of aging effects in varnishes.